GENESIS AND FEATURES OF THE FORMATION OF COLOR IDENTIFICATION BASIC MODELS - Яремчук, О. М.; Кулік, А. В. (Art and Design, 2019)
Purpose. The determination of the formation features of basic models of color and identification of color in the initial stages (the 18th – 19th centuries) of scientific research of the problem. Methodology of the research is based on historical and cultural method. The source base is the artistic, scientific and technical literature of the studied period and also artefacts. Results. This publication reveals a generalized approach to theoretical developments on color perception and identification, and covers the initial period of color research and the formation of basic models of color (the 18th – 19th centuries). So in the middle of the 17th century I. Newton founded a seven-color ordering model, placing them to a closed color circle. At about the same time, other attempts at color systemization were proposed, such as color identification in the form of tables of existing paints, the work of I. Brennen and R. Waller. Subsequently, Jacob Christoph Le Blon concluded that in order to get results, you could use only three colors, namely red, yellow and blue. Based on this work, M. Harris presented his color circle, J. Lambert – a triangular color pyramid, and Ph.Runge built a color sphere using the principle of the globe. Goethe, contrary to Newton’s physical doctrine of colors, conceived another system, it was based on the phenomenological perception of color. According to Goethe and his followers, the colors come from the struggle of "light" and "darkness". A. Schopenhauer took the step that J. Goethe lacked in his thinking: A. Schopenhauer formed a doctrine of color in terms of psychology, noting the enormous role that our brain plays in color perception, and proposing his model of identification by the principle of intensity / extensiveness/quality. for the formal description of the tri-color system of color, forming a mathe-confirmation of T. Young’s theory and came to the conclusion that for the comparison of all shades, three light sources were needed and sufficient: in the red, green and blue parts of the spectrum. The perception of other colors is conditioned by the interaction of these constituents. In his work, J. Maxwell proved that all colors come from a mixture of three spectral colors: red, green, and blue. Based on his research, he introduced the first two-dimensional color spectrum visualization system. H. Grassmann’s merit is the mathematical representation of the three spectral colors. E. Hering’s theory highlights the psychological aspects of color vision: warm sensations occur for white, yellow, and red colors, while cold sensations occur for black, dark blue, and light blue. G. Peano introduced the concept of "color space" as a system of vector space equations.